KINETIC CHARACTERIZATION OF DIFFERENT PHENYTOIN POLYMORPHS BY DSC TECHNIQUE - FLOREZ A., Oscar A.; TOBÓN Z., Gloria E.; LOPERA G., Erika M. (Vitae, 2009)
The activation energy variation can be used as a quick measure to differentiate polymorphs of active pharmaceutical ingredients. In this paper diverse phenytoin crystal habits have been obtained through processes of recrystallization in different solvents. Some of these solids differ in melting point by DSC, but are similar in XRD and FT-IR. From the results of melting point, 4 solids are selected by presenting the most dissimilar values. Their activation energy (Ea) is determined by DSC technique, using 3 theoretical isoconversional nonisothermal models and it is found even that 23 Kcal/ mol of difference separate the most extreme values.